Efektivitas Pelayanan Pengaduan Masyarakat Secara Online Melalui Aplikasi Lapor! (Studi Pada Dinas Komunikasi Dan Informatika Kota Kendari) - Rahmadani, Devi; Tarifu, La; Basri, Muhammad (REZ PUBLICA, 2021)
The study aims to descrie the effectiviness of public complaint services online through the LAPOR! Application. The data analysis method used in this research is descriptive qualitative. This study uses data sourced from primary and secondary data. The results of this study state that the effectiveness of online public complaint services through the LAPOR! It can be said to be effective based on the indicators of measuring the criteria fo effectiveness and quality of public sevices that are good, it’s just that the accuracy indicator of diskominfo as the main admin still has to desseminate information to yhe public that there are some complaints that are not included in the realm of LAPOR!. However, with the LAPOR! As a means of complaint it makes it easier for the public to make a complaint. It is proven that up to September 2020, there were 173 complaints in the application data.